Factors Affecting the Developmental Status of Children Aged 6 Months to 2 Years in Urban and Rural Areas - Rita Andriyani; Eddy Fadlyana; Rodman Tarigan (MDPI AG, 2023)
The first two years of life, including the period from conception to 2 years of age, are very important for a child's growth and development. This study sought to describe the developmental status and the environmental factors that influence it in children aged 6 months to 2 years in urban and rural areas. The research sites were purposively selected: specific health centres in the city of Bandung and West Bandung district were chosen and the study was conducted from November to December 2022. A cross-sectional study was conducted with healthy children aged 6 months to 2 years and their parents, who agreed to participate in the study. Researchers performed developmental tests using the Developmental Pre-screening Questionnaire with classifications for normal developmental test results and developmental delays. During the study, 346 children met the inclusion criteria, resulting in a sample of 164 (47.4%) boys and 182 (52.6%) girls. There were no significant differences among children with developmental delays in urban and rural areas. The factors that influence the possibility of developmental delays in the two research areas were the child's age, exposure to screen time, stimulation, nutritional status, and the use of the mother-child handbook.